Developing “do it yourself” Phantom for Teaching Seldinger Technique in Vascular Access Placement to General Practitioners - Hafidz, Noor; Sedono, Rudyanto; Aditianingsih, Dita; Sugiarto, Adhrie; Manggala, Sidharta Kusuma (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
Establishing a vascular access is a crucial aspect in managing critically ill patients in the Intensive Care Unit (ICU). The skill in placing vascular access varies among healthcare professionals. Clinical experience and level of training among nurses, general practitioners, and intensivists are the determinants of skill in placing vascular access. Training to establish vascular access using the Seldinger technique needs practice using a vascular phantom or a cadaver. Commercially sold phantoms are difficult to get, and an alternative training phantom is needed. We built a simple “do-it-yourself” model of a vascular phantom using “easy-to-find” material that can be used to practice the Seldinger technique. We used a synthetic polyurethane sponge 16x16 cm in size as a base and a polyvinyl alcohol sheet of the same size. We used 22 F urinary catheters trimmed to 12 to represent blood vessels. The final product is a piece of the urinary catheter embedded in the sponge and then covered by polyvinyl alcohol to simulate the epidermis. The phantom can be used in training programs to improve the skill of general practitioners in placing advanced vascular access. 13 general practitioners were involved in this training, and 100% said that this phantom could simulate the experience. “Do-it-yourself” phantom for vascular access training can be used ro practice the Seldinger technique and can simulate the real experience.